TOF method in plasma potential measurements by HIBD - Nedzelskiy, I.S.; Malaquias, A.; Gonçalves, B.; Varandas, C.A.F.; Cabral, J.A.C. (Вопросы атомной науки и техники, 2002)
The heavy ion beam diagnostic (HIBD) developed for the tokamak ISTTOK (R = 0.46 m, a = 0.085 m, B = 0.5 T, I = 6-9 kA) is based on a multiple cell array detector (MCAD), which collects simultaneously a “fan” of secondary ions originated along a primary beam trajectory in collisions with the plasma electrons and separated by the magnetic field of the tokamak. Utilization of the traditional electrostatic energy spectrographs for the plasma potential measurements in experiments with MCAD is very complicated. This paper presents the current results of adaptation and mastering of the alternative time-of-flight (TOF) technique. Three schemes of the measurements are considered: i) “integral” scheme of the average plasma potential measurements by a pulsed primary beam, ii) “quasi-local” scheme of the measurements of plasma potential drop between neighbouring sample volumes, and iii) “local” scheme of plasma potential profile measurements. The electronics used in TOF energy analyzer (TOFEA) consist of charge sensitive and fast shaping amplifiers, constant fraction discriminator and time-toamplitude converter with resolution ∆t/t = 10⁻⁴. The TOFEA resolution ∆t/t = 3×10⁻⁴ has been achieved in mastering experiments with a pulsed (250 ns) primary beam carried out to the primary detector in magnetic field of the tokamak. With plasma the resolution is reduced 2.5 times due to decreasing of signal-to-noise ratio caused by plasma loading of MCAD. The changes of the average plasma potential during discharges with minor disruptions have been obtained by TOF energy analysis. The results of this experiment allow to conclude the reliability of TOF technique in plasma potential measurements by HIBD with MCAD. On the base of the obtained data and experience a four-channel TOFEA for the plasma potential profile measurements has been elaborated.